Dampak notifikasi merger dan akuisisi terhadap return saham pada perusahaan perbankan Indonesia - Juwono, Angela; Widjaja, Audrey Cerelia; Tan, Felice Carmelite Aprilie; Wijaya, Feysya Sandrina; Melinda, Graceline (Nur Science Institute, 2025)
The increase in merger and acquisition activity both globally and nationally, particularly in the Indonesian banking sector, highlights the urgency of conducting an in-depth analysis of its impact on stock prices. This study aims to examine the effect of merger and acquisition announcements on the stock returns of banking companies in Indonesia, focusing on abnormal returns and cumulative abnormal returns during the period from 2020 to 2024. The research employs the event study method with two observation windows: 30 and 90 days, each consisting of 15 and 45 trading days before and after the announcement date. Merger and acquisition announcement data were obtained from the official website of Komisi Pengawas Persaingan Usaha. The sample includes five merger and acquisition events involving Indonesian banking institutions as acquirers, with actively traded shares on the Indonesia Stock Exchange. The results show that merger and acquisition announcements had no significant impact on abnormal returns or cumulative abnormal returns, in either short-term or long-term windows. This condition indicates that the market responded neutrally to the announcements observed.